THE ROLE OF SCAFFOLDING IN THE DECONSTRUCTING OF THINKING STRUCTURE: A CASE STUDY OF PSEUDO-THINKING PROCESS - Imam Kusmaryono; Nila Ubaidah; Mochamad Abdul Basir (IKIP Siliwangi and I-MES, 2020)
This study aimed to (1) analyze the role of scaffolding in deconstructing pseudo-thinking structure, and (2) analyze the development of students' thinking structures after receiving scaffolding. The study was framed with a qualitative methodology by involving case study design. This research was conducted at State Junior High School 31 in Semarang City, Indonesia. Data was collected through tests, observation, and interview methods. Result of the study indicated that (1) scaffolding has changed the pseudo thinking process into a real thought process, and (2) scaffolding could develop students’ thinking structure into a more complex (abstract) level. Their thinking structure was initially on the stage of comparative thinking structure before receiving scaffolding assistance and after receiving scaffolding, to developed into the stage of logical reasoning thinking structure. In other words, scaffolding could become a useful strategy to help students go through different Zone of Proximal Development (ZPD).